Call for a Uniform Strategy of Collecting Alzheimer's Disease Costs: A Review and Meta-Analysis - Marešová, Petra; Dolejš, Josef; Kuca, Kamil (Journal of Alzheimer's disease, 2018)
BACKGROUND: There is now a general attempt in developed countries to implement strategic plans to fight against Alzheimer's disease and other dementia disorders. Among others, attention is paid to the issues of registers and calculations of economic burden. Currently available calculations of costs are difficult to compare. The problem is a different breakdown of cost categories and non-unified monitoring of cost types. OBJECTIVE: The aim of this paper is to note the problem of poor availability and inconsistencies in cost monitoring. Furthermore, the intersection of cost items that are comparable and consistently monitored in expert studies are specified. METHODS: The Web of Science, Elsevier Science Direct, PubMed, and Scopus databases are used in a systematic review. Two independent reviewers screened the identified records and selected relevant articles published in the period from 2010 to 2016. A meta-analysis of costs is performed in four categories related to patients suffering from Alzheimer's disease. RESULTS: The resulting estimation of total costs per patient per month through meta-analysis is € 3,896, with 95% CI [2078, 5713]. The highest costs arise from informal care following non-medical and medical care. CONCLUSION: The results confirm assumption that inconsistencies in cost monitoring of the treatment and care of people with dementia exists in Europe. Homogeneity could be assumed only in the medical costs of severe patients. Heterogeneity is assumed in non-medical costs, informal costs. Cost items should be defined and collected more precisely for future more precise monitoring of the economic burden.
Keywords: databáze bibliografické; Cost of Illness; meta-analysis; developed countries; osobní újma zaviněná nemocí; Humans; lidé; analýza nákladů a výnosů; Alzheimer Disease; Cost-Benefit Analysis; Alzheimerova nemoc; Databases, Bibliographic; Delivery of Health Care; Alzheimer’s disease; data collection uniformity; poskytování zdravotní péče